Sandwich Antibody Arrays Using Recombinant Antibody-Binding Protein L - Seo, Jin-soo (American Chemical Society, 2014)
[Image: see text] Antibody arrays are a useful for detecting antigens and other antibodies. This technique typically requires a uniform and well-defined orientation of antibodies attached to a surface for optimal performance. A uniform orientation can be achieved by modification of antibodies to include a single site for attachment. Thus, uniformly oriented antibody arrays require a bioengineered modification for the antibodies directly immobilization on the solid surface. In this study, we describe a “sandwich-type” antibody array where unmodified antibodies are oriented through binding with regioselectively immobilized recombinant antibody-binding protein L. Recombinant proL-CVIA bearing C-terminal CVIA motif is post-translationally modified with an alkyne group by protein farnesyltransferase (PFTase) at the cysteine residue in the CVIA sequence to give proL-CVIApf, which is covalently attached to an azido-modified glass slide by a Huisgen [3 + 2] cycloaddition reaction. Slides bearing antibodies bound to slides coated with regioselectively immobilized proL-CVIApf gave stronger fluorescence outputs and those where the antibody-binding protein was immobilized in random orientations on an epoxy-modified slide. Properly selected capture and detection antibodies did not cross-react with immobilized proL-CVIApf in sandwich arrays, and the proL-CVIApf slides can be used for multiple cycles of detected over a period of several months.